The Students’ Misconception on Mixed Arithmetic Operations in SDN 8 Pahandut Palangka Raya - Janu Pinardi; Abdul Rahman Azahari; Bejo Basuki (JURNAL PENDIDIKAN, 2021)
Abstract The study aims to determine: (1) the kinds of student misconceptions, and (2) the causes of student misconceptions The results showed that the kinds of misconceptions were: (1) translation misconceptions, which were caused by a lack of understanding changing the language in the questions into the correct mathematical language, (2) conceptual misconceptions, which is caused by students not understanding the definition of basic arithmetic operations, (3) strategic misconceptions, which are caused by students not correctly selecting and determining procedures and properties, arithmetic operations correctly, (4) systematic misconceptions, which are caused because students experience errors or are incomplete and precise in writing down the steps to solve the problem (5) sign misconceptions, which are caused by students not knowing which arithmetic operations to do first, (6) misconceptions of counting, that is as a result of students making mistakes in performing mixed arithmetic operations.